Refolding of full-length alpha-fetoprotein (F-AFP). - Chandra, Kelvin. (2009)
Alpha-fetoprotein (AFP) is a promising polypeptide for the treatment of several autoimmune diseases. The denatured-reduced recombinant human (rhAFP) was successfully refolded previously by dilution and dialysis refolding. However, the refolding of the denatured-reduced full-length AFP (FL-AFP) with signal peptide at the N-terminus of the AFP has not been studied before. Other studies on the effect of the signal peptides on its protein refolding showed the recovery of the protein activity, suggesting that the protein or enzyme was successfully refolded. In this study, the refolding of the Arginine AFP (A-AFP) and FL-AFP was performed by dilution and dialysis in a refolding buffer. The refolding yield of A-AFP was approximately 48% as assessed by RP-HPLC. The denatured-reduced of the FL-AFP was not refolded successfully. It was believed that the hydrophobic signal peptides affected the RP-HPLC profile in the retention time resulting in the same retention of the denatured-reduced and the refolded FL-AFP.